Development and acceptance of online assessment in higher education: Recommendations for further research (Journal of Applied Learning and Teaching, 2022)
Online assessment is now used commonly in higher education institutions. While this approach to assessment has several advantages over paper-based assessments, its introduction often precipitates concerns from users, in particular, students and academic staff members. This paper traces the development of online assessment and reviews studies published on student and teacher perceptions of online assessment over a 15-year period. Studies suggest that while students’ perceptions are generally found to be positive, academic staff members’ perceptions have been more mixed. Recommendations for future research into teachers’ responses to online assessment tools are made.